MicroRNA transcriptome analysis reveals the potential role of miRNAs in regulating adipocyte hyperplasia and hypertrophy - Ni, Ligang; Gu, Zhanpeng; Wang, Xiaoyan; Zhang, Junsheng; Zhou, Chunbao; Zhang, Yaqin; Gao, Huizhen; Xu, Pan (Frontiers in Genetics, 2026)
BackgroundMicroRNAs (miRNAs) play a crucial role in regulating the development of backfat, yet their specific regulatory functions remain incompletely understood. The main objective of this study was to reveal the regulatory mechanism of miRNAs in porcine backfat development, and the molecular regulatory mechanisms of adipocyte hyperplasia and hypertrophy.Methods and resultsIn this study, we used high‐throughput sequencing technology to construct miRNA expression profiles of backfat tissue from Sujiang pigs at four developmental stages: 1, 3, 6, and 8 months old. A total of 292 known miRNAs and 274 novel miRNAs were identified. Through a comprehensive analysis of the miRNA and messenger RNA (mRNA) transcriptomes, we discovered many important mRNA‐miRNA pairs during porcine backfat development. Functional analysis revealed that the PI3K‐Akt signaling pathway, signaling pathways regulating pluripotency of stem cells, and mTOR signaling pathway as pivotal pathways related to adipocyte differentiation and hyperplasia. Butanoate metabolism, fatty acid metabolism, and fatty acid degradation were identified as pivotal pathways related to adipocyte metabolism and hypertrophy. Ssc‐miR‐1343, ssc‐miR‐1307, ssc‐miR‐1249, ssc‐miR‐331-3p, ssc‐miR‐296‐5p, ssc‐miR‐149, ssc‐miR‐361‐3p, and ssc‐miR‐615, which were identified as hub miRNAs in the miRNA‐mRNA regulatory network, may play crucial roles in regulating backfat development. Further validation revealed that ssc‐miR‐1343 can directly target the TCF3 and FASN genes at different backfat developmental stages, potentially regulating adipocyte hyperplasia and hypertrophy.ConclusionThe comparative miRNA and mRNA transcriptomes analysis of porcine backfat tissue revealed the molecular regulatory mechanisms involved in porcine backfat development, providing useful information for the future breeding of pigs.